Self-Illuminating Agents for Deep-Tissue Optical Imaging - Li, Qing; Zeng, Jianfeng; Miao, Qingqing; Gao, Mingyuan (Frontiers in Bioengineering and Biotechnology, 2019)
Optical imaging plays an indispensable role in biology and medicine attributing to its noninvasiveness, high spatiotemporal resolution, and high sensitivity. However, as a conventional optical imaging modality, fluorescence imaging confronts issues of shallow imaging depth due to the need for real-time light excitation which produces tissue autofluorescence. By contrast, self-luminescence imaging eliminates the concurrent light excitation, permitting deeper imaging depth and higher signal-to-noise ratio (SNR), which has attracted growing attention. Herein, this review summarizes the progress on the development of near-infrared (NIR) emitting self-luminescence agents in deep-tissue optical imaging with highlighting the design principles including molecular- and nano-engineering approaches. Finally, it discusses current challenges and guidelines to develop more effective self-illuminating agents for biomedical diagnosis and treatment.